A newly defined basement membrane-related gene signature for the prognosis of clear-cell renal cell carcinoma - Zhou, Tao; Chen, Weikang; Wu, Zhigang; Cai, Jian; Zhou, Chaofeng (Frontiers in Genetics, 2022)
Backgroud: Basement membranes(BMs) is significantly associated with cell polarity, differentiation, migration, and survival. Besides, previous studies have showed that BMs play key role in the progression of cancer and it can be termed as potential target in inhibiting the development of cancer. However, the association between basement membrane related genes(BMRGs) and clear cell renal cell carcinoma(ccRCC) is remain unclear.Therefore, we constructed a novel risk signature according to BMRGs to explore the relationship between ccRCC and BM. Methods: We gathered transcriptome and clinical data from The Cancer Genome Atlas (TCGA) and randomly separated the total set into training and test sets with a 1:1 ratio to explore new possible biomarkers and create a BMRGs predictive signature of ccRCC. Pearson correlation analysis(|coefficients| > 0.4, and p<0.001) was carried out to identify the BMRGs. Then, we applied univariate Cox regression and least absolute shrinkage and selection operator (LASSO) Cox regression analysis to establish the mold. The risk signature was further verified and evaluated through principal component analysis (PCA), the Kaplan-Meier technique, and time-dependent receiver operating characteristics (ROC). And a nomogram was designed to predict the overall survival (OS). The possible biological pathways were investigated through functional enrichment analysis. In this study, we also carried out tumor mutation burden (TMB), immunological analysis and immunotherapeutic drug analysis between high and low-risk groups. Result: We identified 33 differently expressed genes, and constructed a risk mold of 8 BMRGs, including COL4A4, FREM1, CSPG4, COL4A5, ITGB6, ADAMTS14, MMP17, THBS4. The PCA analysis exhibited that the signature can distinguish the high and low-risk groups well. Besides, The K-M and ROC analysis showed that the mold could predict the prognosis well with the area under the curves(AUC) was 0.731. Moreover, a nomogram showed good prediction. Univariate and multivariate Cox regression analysis validated that the 8 BMRGs mold was an independent risk factor for ccRCC. Furthermore, immune cell infiltration, immunological checkpoint, TMB and half-inhibitory concentration varied considerably among high and low-risk groups. Conclusion: Employing the 8 BMRGs risk mold as a prognostic indicator might provide us with the development of ccRCC as well as therapy response prediction.